2016
DOI: 10.1037/sgd0000177
|View full text |Cite
|
Sign up to set email alerts
|

Missteps in psychotherapy with transgender clients: Promoting gender sensitivity in counseling and psychological practice.

Abstract: Transgender and gender nonconforming (TGNC) clients often report negative experiences in the receipt of medical and mental health services (Poteat, German, & Kerrigan, 2013;Shipherd, Green, & Abramovitz, 2010;Xavier et al., 2013). Problematic psychotherapy experiences can impact symptom severity, treatment satisfaction, and help-seeking (Bockting, Robinson, Benner, & Scheltema, 2004;Willging, Salvador, & Kano, 2006). The present grounded theory study was conducted with 45 TGNC participants to identify the spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
152
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(161 citation statements)
references
References 24 publications
7
152
0
2
Order By: Relevance
“…Also, it has been reported that clinicians, in the absence of solid TGNC affirmative training and awareness, may be biased in pathologizing transgender applicants for medical treatments. For instance, in a qualitative study with 45 TGNC participants, Mizock and Lundquist [56] identified specific missteps psychotherapists make in working with this vulnerable group, including gender pathologizing. Clinician bias against transgender clients has been also documented in experimental studies using case reports of fictitious patients [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Also, it has been reported that clinicians, in the absence of solid TGNC affirmative training and awareness, may be biased in pathologizing transgender applicants for medical treatments. For instance, in a qualitative study with 45 TGNC participants, Mizock and Lundquist [56] identified specific missteps psychotherapists make in working with this vulnerable group, including gender pathologizing. Clinician bias against transgender clients has been also documented in experimental studies using case reports of fictitious patients [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Mizock and Lundquist add onto the American Psychological Association's (APA) guidelines by going over some of the possible missteps a mental health practitioner can make with transgender clients. 38 These include placing the burden of education on the client instead of doing independent research, overlooking important aspects of the client's life unrelated to gender, and acting as gatekeeper to gender affirmative resources. Singh and Dickey call practitioners to action by elaborating on some of the tenants of the APA guidelines.…”
Section: Resultsmentioning
confidence: 99%
“…Through ignorance, psychotherapists may commit a multitude of micro‐aggressions, such as asking for multiple clarifications or using inappropriate language or restrictive gender conceptualisations (Mizock & Lundquist, ). Those with “gender narrowing” tendencies may further reify traditional notions of gender and impose their implicit attitudes about gender onto the client.…”
Section: Supporting Gender Diversity In Clinical Practice and Promotimentioning
confidence: 99%
“…Trans individuals reported their psychotherapists conducting sessions as if their transgender identity were a problem to be “fixed” or responsible for all their other problems. This process, known as gender repairing, inadvertently pathologised or stigmatised clients as mentally ill (Mizock & Lundquist, ). Reparative therapies have been used with LGBTI+ individuals in an attempt to change the person's gender or sexual orientation to the dominant, societal norm.…”
Section: Supporting Gender Diversity In Clinical Practice and Promotimentioning
confidence: 99%